2007
DOI: 10.1097/01.olq.0000253346.41123.7c
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Sexually Transmitted Disease Diagnostic Technologies in California, 1996–2003

Abstract: Analyzing trends in diagnostic technologies enhances our understanding of the epidemiology of STDs and monitoring laboratory capacity and practices facilitates implementation of STD control activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A survey of laboratories in the District of Columbia that reported gonorrhea results to the health department demonstrated that among laboratories that conducted gonorrhea cultures, only one third performed antibiotic susceptibility testing (51). A study of clinical laboratories in California reported that gonorrhea culture testing has substantially decreased and gonorrhea and chlamydia tests performed using NAAT have increased over time (52). For detection of herpes simplex virus (HSV), direct antigen and culture testing on lesions have decreased over time and serologic testing has increased (52).…”
Section: Current Practice On Selected Clinical Services In the Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of laboratories in the District of Columbia that reported gonorrhea results to the health department demonstrated that among laboratories that conducted gonorrhea cultures, only one third performed antibiotic susceptibility testing (51). A study of clinical laboratories in California reported that gonorrhea culture testing has substantially decreased and gonorrhea and chlamydia tests performed using NAAT have increased over time (52). For detection of herpes simplex virus (HSV), direct antigen and culture testing on lesions have decreased over time and serologic testing has increased (52).…”
Section: Current Practice On Selected Clinical Services In the Unitedmentioning
confidence: 99%
“…A study of clinical laboratories in California reported that gonorrhea culture testing has substantially decreased and gonorrhea and chlamydia tests performed using NAAT have increased over time (52). For detection of herpes simplex virus (HSV), direct antigen and culture testing on lesions have decreased over time and serologic testing has increased (52).…”
Section: Current Practice On Selected Clinical Services In the Unitedmentioning
confidence: 99%
“…In California, the proportion of gonorrhea testing performed using PCR test increased from 1-59% and culture test decreased from 42-10% of all gonorrhea testing. [34] In contrast, the availability of PCR test was still as low as 15% among hospitals providing STI clinical service in Shandong province in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring trends in the use of diagnostic methods enhances STI control efforts by improving the interpretation of STI trends, creating valuable partnerships with laboratories, facilitating the evaluation of screening programs and investigating outbreaks [28]. With the continuous development and improvement of diagnostic methods it is obvious that there have been changes since this survey was performed.…”
Section: Discussionmentioning
confidence: 99%